A new class of distribution having decreasing, increasing, and bathtub-shaped failure rate. Issue 20 (18th October 2017) - Maurya, S. K.; Kaushik, A.; Singh, S. K.; Singh, U.
ABSTRACT: In this article, we propose a new class of distribution which is based on the concept of exponentiated generalization with some modification so as to provide a better result in terms of flexibility. Our proposed distribution accommodates various shapes of hazard rate including the bathtub. Exponential distribution has been taken as the baseline distribution. Various statistical properties of the proposed distribution have been studied. We have used the method of maximum likelihood for estimation of the parameters of the proposed model. Last, we have analyzed four real datasets to illustrate the flexibility of the model in comparison to eight existing well-known distributions.